RAPD Markers Distinguish Ground Beetle Species Using Genetic Polymorphism - Humadi, Ashwak T.; Sultan, Ammar Ahmed; Khaled, Shifaa Waleed (Universitas Muhammadiyah Sidoarjo, 2024)
This study focuses on differentiating between two ground beetle species, Oryctes rhinoceros and Allomyrina dichotoma, using RAPD markers due to the limitations of phenotypic methods. Ten RAPD primers were employed to identify polymorphic markers. Results showed a total of 41 polymorphic bands, with primers OP-C06 and OP-C15 displaying significant variation in polymorphism percentages, 100% and 16.7% respectively. Primer OP-A08 demonstrated the highest efficiency rate (17.07%) and effectively distinguished between the two beetle species, unlike primers OP-B09, OP-B14, and OP-C10, which showed zero polymorphism. This study underscores the utility of RAPD markers, particularly OP-A08, in accurately identifying insect species, thereby advancing genetic classification techniques. Highlights: Effective Distinction: OP-A08 distinguished Oryctes rhinoceros and Allomyrina dichotoma. High Efficiency: OP-A08 had the highest efficiency rate at 17.07%. Reliable Classification: RAPD markers outperform phenotypic methods for insect identification. Keywords: RAPD Markers, Genetic Polymorphism, Ground Beetles, Insect Classification, Molecular Genetics